(untitled) (Revista de Crítica Literaria Latinoamericana, 2022)
In this essay I argue that in the novel Las aventuras de la China Iron Gabriela Cabezón Cámara constructs a decolonial queer-femme pedagogy, particularly, through a trans imaginary that polemicizes with the modern, colonial and patriarchal regime. This allows her to offer new perspectives of encounter with the human and non-human world. On the one hand, I argue that the trans appears in the text as an escape and displacement from the fixed and stagnant rhetoric of the colonialist and patriarchal constructs of nation-states to configure what I call here a transnation. On the other hand, I argue that the protagonist of the novel undertakes a journey from the discovery and apprehension of colonial matrices to a detachment from them, through decolonizing communal practices that embrace perspectives decentered from the Eurocentric lens.